1992
DOI: 10.1007/bf00133465
|View full text |Cite
|
Sign up to set email alerts
|

Suppression by interferon-? of tumor cell-induced increase in mesothelial permeability

Abstract: The effect of interferon-gamma (IFN-gamma) on the interaction between tumor cells and mesothelial cell layers was studied from the aspect of changes in mesothelial permeability. Mesothelial permeability was assessed as the percentage diffusion of radiolabeled albumin across the mesothelial cell sheets on Matrigel-coated filter cup assemblies. When lined gastric carcinoma cells (KATO-III) were seeded on the confluent mesothelial cell layers, the fine cobblestone appearance of the cell sheet was disrupted and me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1995
1995
1996
1996

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 13 publications
1
3
0
Order By: Relevance
“…In this regard, Uchiyama et al have reported that addition of tumor cells to mesothelial cell monolayers in vitro, directly or indirectly (by secretion of factors) induced mesothelial cell retraction and a disruption of the peritoneal cell monolayer. They further demonstrated that this phenomenon was inhibited by IFN-7 treatment of the mesothelial cells and, interestingly, also reported that IFN-3, seemed to act directly on the mesothelial cells to induce some resistant mechanisms against tumor cells as we report in this study (38). Taken together--the fact that other reports have shown in vivo responsiveness to IFN-1 and TNF-~ treatment in ovarian cancer patients--this further supports our findings of a possible positive role of normal peritoneal mesothelial cells in the pathobiology of ovarian carcinoma.…”
Section: Discussionsupporting
confidence: 81%
“…In this regard, Uchiyama et al have reported that addition of tumor cells to mesothelial cell monolayers in vitro, directly or indirectly (by secretion of factors) induced mesothelial cell retraction and a disruption of the peritoneal cell monolayer. They further demonstrated that this phenomenon was inhibited by IFN-7 treatment of the mesothelial cells and, interestingly, also reported that IFN-3, seemed to act directly on the mesothelial cells to induce some resistant mechanisms against tumor cells as we report in this study (38). Taken together--the fact that other reports have shown in vivo responsiveness to IFN-1 and TNF-~ treatment in ovarian cancer patients--this further supports our findings of a possible positive role of normal peritoneal mesothelial cells in the pathobiology of ovarian carcinoma.…”
Section: Discussionsupporting
confidence: 81%
“…The combination of PKH26 labelling with laser confocal scanning microscopy (LCSM) clearly identified SST-2 cells interacting with the mesothelial cell monolayer at a specific depth. Thus, the number of attached or penetrating SST-2 cells was quanitified by LCSM ( Figure 6) (van Hinsbergh et al, 1990;Pronk et al, 1993;Uchiyama et al, 1992) or hernia sac (Donna et al, 1989) and pleural tissues (Asplund and Heldin, 1994;Horai et al, 1992). However, these materials are not always available and their cellular features may vary from case to case.…”
Section: Ter Measurementsmentioning
confidence: 99%
“…It is generally agreed that transmesothelial penetration by cancer cells occurs at the junctional region between adjacent cells. It has been reported that cancer cells induce morphological changes of mesothelial cells by releasing some unknown substances (Kimura et al, 1985;Uchiyama et al, 1992) and may damage the mesothelial cells by attachment onto the mesothelial surface (Kiyasu et al, 1981). In cultured endothelial cells, several substances, including thrombin (Laposata et al, 1983), active oxygen (Shasby et al, 1985), 12(S)-HETE (Tang et al, 1993), tumour necrosis factor, interferon-y, interleukin 1 (Molony and Armstrong, 1991), histamine (Carson et al, 1989) and tyrosine phosphatase inhibitor (Staddon et al, 1995), are confirmed to increase permeability.…”
Section: Ter Measurementsmentioning
confidence: 99%
“…The invasive response of colon carcinoma cells to HGF was assessed by a standard chemoinvasion assay using microplate Transwell chambers, prepared as previously described [Uchiyama et al, 1992;Mareel et al, 19911. The 9-mm diameter filters of 8-Fm porous cell culture Transwell inserts (Falcon, Indianapolis, IN) were coated with 100 Fg basement membrane matrix, Matrigel (Collaborative Research, Bedford, MA).…”
Section: Migration and Cell-matrix Invasion Assaymentioning
confidence: 99%